Mechanistic Studies of the Skin Delivery of Lipid Colloid Systems with Different Oil/Fatty Ester Ratios for Both Lipophilic and Hydrophilic Drugs - Hsu, Shu-Hui; A. Al-Suwayeh, Saleh; Hung, Chi-Feng; Tsai, Chia-Yin; Fang, Jia-You (Current Nanoscience, 2011)
The aim of the present work was to evaluate the effects of lipid colloid systems on skin permeation of two antipsoriatic drugs, calcipotriol and methotrexate. Colloidal systems made of Precirol (solid lipid nanoparticles, SLN), Precirol+squalene (nanostructured lipid carriers, NLC), and squalene (lipid emulsions, LE) as the lipid core material were prepared. Calcipotriol was encapsulated in the inner phase of these carriers due to its high lipophilicity. The hydrophilic methotrexate resided in the aqueous phase of the systems. Particle sizes of SLN, NLC, and LE were 303, 192, and 212 nm, respectively. LE showed a lower negative zeta potential (-20 mV) compared to SLN and NLC (-30 mV). In vitro skin permeation was measured with a Franz assembly. The results showed that lipid colloids increased calcipotriol permeation via nude mouse skin by 2.6∼3.2-fold over the aqueous control. Application of lipid colloids enhanced methotrexate penetration by 4.5∼10.8-fold. Drug permeation was affected by the composition of the inner phases. The permeation of both drugs generally showed a trend of NLC > LE > SLN. The mechanisms of the permeation enhancement by nanoparticles were elucidated using various barriers against drug permeation, including delipidized skin, hairy mouse skin, and cellulose membranes. We determined that the release rate, partitioning ability to the skin, and enhancer effect were major factors enhancing drug permeation. Occlusiveness and follicular pathways were less important for calcipotriol and methotrexate delivery. The in vivo confocal laser scanning microscopic profiles confirmed the importance of the partitioning process for lipophilic drugs. The in vivo examination of transepidermal water loss demonstrated the maintenance of skin integrity after a 24-h application of lipid colloid systems.
Keywords: Drug permeation